Centella asiatica extract in carboxymethyl cellulose at its optimal concentration improved wound healing in mice model. Issue 12 (December 2022) - Tanga, Bereket Molla; Bang, Seonggyu; Fang, Xun; Seo, Chaerim; De Zoysa, Mahanama; Saadeldin, Islam M.; Lee, Sanghoon; Park, Sang Un; Chung, Sun-Ok; Lee, Geung-Joo; Cho, Jongki
Abstract: Centella asiatica (C. asiatica) has reported to be one of the traditional herbal remedies, whereas poor water solubility leads to lower bioavailability thereby affecting it remedial efficacy. Therefore, we aimed to evaluate its efficacy through increased bioavailability by using high viscosity Carboxymethyl Cellulose (CMC) as solvent on methanol-based extract on wound healing, in vivo . The preparation was applied as 0.0% (control, CMC alone), 0.25. 0.5 and 1% concentrations of extract of C. asiatica . We evaluated the efficiency of preparations on wound healing progression as progression of wound contraction, tissue proliferation and cells deposition, and relative level of gene expression for genes associated with wound healing. The results showed that 0.5% extract in CMC had significantly higher ( P < 0.05 ) wound contraction than control and other concentrations. The level tissue deposition and the infiltration of polymorphonuclear cells in groups treated with 0.5 % concentration preparation were higher than that other treatments and control. Similarly, the relative level of gene expression in 0.5% concentration treated group were statistically significantly higher ( P < 0.05 ) than that of control. It is believed that the lower concentration of the extract would have lessor effect on wound healing, whereas higher concertation would be interfering the optimal inflammatory tissue deposition; and there by negatively affecting wound healing. The results indicated that C. asiatica can be optimally used at 0.5 % of extract in CMC for wound healing as indicated by speeding the progression of wound closure and by increasing the expression of collagen II and III together with reducing the expression of TGFβ1. However, higher concentrations of the crude extract of C. asiatica could paradoxically resulting in undesired effects. It is recommended that further evaluation should be performed on wider scale and the economic feasibility evaluation should be performed. Abstract : Centella asiatica ; Inflammation; Mice; Polymorphonuclear cells; Wound healing.